Kakeksia Kardiak: Implikasi Klinis, Prevensi, dan Tatalaksana - Sidhi Laksono; Reynaldo Halomoan (Universitas Muhammadiyah Semarang, 2020)
Patients with cardiovascular diseases such as chronic heart failure may develop cardiac cachexia. This occurs due to various mechanisms associated with pathological processes in the heart. The incidence of cardiac cachexia is also a marker of poor prognosis in patients. This condition is characterized by weight loss in patients and a decrease in muscle mass. We conducted a manual search method to find the topic-related article. A total of 30 relevant works of literature were studied. We aimed to understand the role of cardiac cachexia on the physiological function and its proper management. From our study, it wasfound that systemic inflammation had a role in the development of cardiac cachexia. The presence of cardiac cachexia is associated with the disruption in several systems such as cardiovascular, gastrointestinal, and also the immune system. Strategies for prevention and appropriate management will reduce the incidence of this event. The treatment given can be pharmacological and non-pharmacological. In conclusion, cardiac cachexia impairs the functional capacity of the patient. Proper management can reduce the mortality and morbidity in patients with cardiac cachexia.Keywords: Cardiac cachexia, physiological function, preventive and management